2021
DOI: 10.3390/f12091268
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Antifungal Properties of Four Thaumatin-like Proteins in Spruce (Picea likiangensis)

Abstract: Thaumatin-like proteins (TLPs) are involved in the plant defense response against pathogens, and most of them exhibit antifungal activity. However, the role of TLPs in pathogen-induced defense responses in spruce is not fully understood. In this study, four TLP genes encoding thaumatin-like protein, designated as PlTLP1–4, were isolated and identified from Picea likiangensis needles. Sequence analysis showed that PlTLP1, PlTLP3, and PlTLP4 contained 16 conserved cysteine residues, while PlTLP2 had only 10 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Two primer pairs, PaPR4-a-Fq/PaPR4-a-Rq and PaPR4-b-Fq/PaPR4-b-Rq ( Supplementary Table S1 ), were designed for RT-qPCR based on the sequences of PaPR4-a and PaPR4-b . EF (GenBank ID: AJ132534.1) and TIF (GenBank ID: DR448953.1) were used as the internal reference genes ( Supplementary Table S1 ) [ 75 , 76 , 77 ]. Hieff UNICON ® Universal Blue qPCR SYBR Green Master Mix (Yeasen Biotechnology Co., Ltd., Shanghai, China) was used for RT-qPCR, and the experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Two primer pairs, PaPR4-a-Fq/PaPR4-a-Rq and PaPR4-b-Fq/PaPR4-b-Rq ( Supplementary Table S1 ), were designed for RT-qPCR based on the sequences of PaPR4-a and PaPR4-b . EF (GenBank ID: AJ132534.1) and TIF (GenBank ID: DR448953.1) were used as the internal reference genes ( Supplementary Table S1 ) [ 75 , 76 , 77 ]. Hieff UNICON ® Universal Blue qPCR SYBR Green Master Mix (Yeasen Biotechnology Co., Ltd., Shanghai, China) was used for RT-qPCR, and the experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…A TLP gene was identified in a GWAS as one hub gene of importance for pine tree breeding (Ding et al 2022b). The antifungal activity of Picea TLPs is based on glucanase activity on fungal hyphal cell walls (Liu et al 2021(Liu et al , 2022.…”
Section: Small Secreted Proteins and Their Functionsmentioning
confidence: 99%
“…As a positive consequence of the new technical approaches in -omics research [1] and the continuous decrease in sequencing and other molecular biology techniques costs, the papers do not merely focus on model species. Indeed, six papers focus on broadleaved trees and four on conifers, including economically relevant species for a plethora of different uses, but also rare/endangered species [3] and ecologically important trees [4,5]. The variety of different species studied by the research papers belonging to this Special Issue perfectly respond to the invitation reported in [2], to extend the research fields in forest genetics to a broader number of species.…”
mentioning
confidence: 99%
“…In particular, [6] analyzes Camellia oleifera, which is used for oil production; [7] Liriodendron sino-americanum, a relevant ornamental and afforestation species; and [3] Handeliodendron bodinieri, a rare and endangered species, which is also important for bio-energy, landscaping, and water and soil conservation. The of [4] focuses on Picea likiangensis, one of the dominant tree species in the subalpine forest southwest China, with an important ecological in soil and water and carbon storage; [8] reports findings on Pinus massoniana, a relevant timber well as loblolly and slash pines studied in [9]. Chosenia arbutifolia [10] is used as a raw material for technological aims and for landscape planting in China.…”
mentioning
confidence: 99%